Concepts, Applications and Emerging Opportunities in Industrial Engineering 2021
DOI: 10.5772/intechopen.93276
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Lean-Green-Six Sigma Practices to Improve the Performance of the Manufacturing Industry

Abstract: To survive in the global competitive market, the manufacturing organization must adopt changes in technologies and strategies into their processes on a continuous basis. So, nowadays, Lean, Green, and Six Sigma became business process strategies, which are employed in most of the organization to enhance their manufacturing performance. However, the significant information is that these strategies are implemented sequentially instead of simultaneously. The objective of this chapter is to propose an integrated L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Based on the analysis of the previous studies of MM, nine CSFs constructs having the most substantial impact in MM implementation were summarized using the affinity diagram technique [6,26]. This technique comprises of three steps, namely: Step 1: Extracting the key points of CSFs from literature sources (journals, books, etc.…”
Section: -Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the analysis of the previous studies of MM, nine CSFs constructs having the most substantial impact in MM implementation were summarized using the affinity diagram technique [6,26]. This technique comprises of three steps, namely: Step 1: Extracting the key points of CSFs from literature sources (journals, books, etc.…”
Section: -Methodologymentioning
confidence: 99%
“…Through a systematic and strategic maintenance management (MM), defects and variations resulting from the poor equipment could be eliminated [4,5]. Hence, equipment efficiency should include product quality index as well rather than focusing on the equipment availability alone [6]. However, it is observed that the significant role of MM as an important constituent of QI initiatives is not emphasized in the literature, particularly in Small and Medium-sized Enterprises (SMEs) [6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation